2013
DOI: 10.9787/kjbs.2013.45.3.273
|View full text |Cite
|
Sign up to set email alerts
|

A New Soybean Cultivar ‘Wonheug’ for Sprout with Small Seed, Black Seed Coat and Disease Tolerance

Abstract: A new soybean cultivar for soybean sprout, 'Wonheug' was developed at the National Institute of Crop Science (NICS) in 2009. 'Wonheug (Iksan63)' was released from the cross between F1 of YS1286 (Tawonkong/Jinju#1) and Jinju#1. It has purple flower, oval shaped leaf, tawny pubescence and small black seed (8.8 g/100 seed). Maturing date of 'Wonheug' is ten days later than check cultivar, 'Tawonkong'. Even though mosaic symptom can be observed by artificial inoculation, 'Wonheug' is tolerant to virus and bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The cultivars, Pungwon (Oh et al 2007c) and Wonhwang (Oh et al 2007b) had isoflavone contents of 5,935 g/g and 5,370 g/g, respectively. Similarly, the cultivar Tawonkong ) was reported to have low sprout isoflavone content (Kim et al 2013). Isoflavone content in soybean seed and sprouts not only depends on the soybean cultivar, but it is also affected by the year of seed production, temperature, light and soybean field conditions (Hoeck et al 2000;Xu et al 2003;Seguin et al 2004;Zhu et al 2005).…”
Section: Isoflavone Contentmentioning
confidence: 98%
See 3 more Smart Citations
“…The cultivars, Pungwon (Oh et al 2007c) and Wonhwang (Oh et al 2007b) had isoflavone contents of 5,935 g/g and 5,370 g/g, respectively. Similarly, the cultivar Tawonkong ) was reported to have low sprout isoflavone content (Kim et al 2013). Isoflavone content in soybean seed and sprouts not only depends on the soybean cultivar, but it is also affected by the year of seed production, temperature, light and soybean field conditions (Hoeck et al 2000;Xu et al 2003;Seguin et al 2004;Zhu et al 2005).…”
Section: Isoflavone Contentmentioning
confidence: 98%
“…Lee and Chung (1982) reported an increase in the crude protein content, whereas Choi et al (2000b) reported a decrease in the crude protein levels after 5 days of sprouting. Soybean sprouts contain high amounts of essential and non-essential amino acids Suh et al 2004;Oh et al 2005;Park et al 2005;Yun et al 2005;Oh et al 2006a;Oh et al 2006b;Oh et al 2007a;Oh et al 2007b;Oh et al 2007c;Oh et al 2008;Phommalth et al 2008;Cho et al 2009;Oh et al 2009a;Oh et al 2009b;Kim et al 2013) ( Table 1). The concentration of the total amino acids varies across different soybean genotypes (Table 1) and during the days of sprouting (Song et al 2000).…”
Section: Amino Acid and Protein Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Selama perkecambahan terjadi perubahan morfologi, fisiologi, dan biokimia pada biji kedelai. Pada awal proses perkecambahan terjadi perombakan protein oleh enzim proteolitik menjadi asam amino sehingga meningkat jumlah dan ketersediaannya secara biologi (bioavailability) (Aminah 2010;Shi et al 2010;Guo et al 2012;Kim et al 2013;Warle et al 2015;Gan et al 2016). Demikian pula kandungan lutein dan betakaroten yang memiliki aktivitas antioksidan meningkat (Cazzonelli 2011).…”
Section: Pendahuluanunclassified